MANAGEMENT OF GRAHANI WITH YOGA AND KAAL BASTI – A CASE REPORT - Chougule Paresh R. (International Journal of Applied Ayurved Research, 2017)
In this modern era Grahani disease has great importance due to straight relation of inappropriate food habits as well as changing lifestyle. Always one to one correlation of Ayurvedic disease with modern science is not possible but taking into consideration the dysfunction of Agni is accountable for undigested food which is responsible for various functional as well as structural defects in the gastro-intestinal tract. Hence IBS could be considered for the same. The prevalence of IBS varies across the world, ranging from as high as 10%-20% in the West, to as low as 4.2% in India. A 36 years old male patient suffering from Grahani disease was planned for two phase basti treatment course. First phase with Yoga basti course and second with Kaal basti course. After completion of 2nd phase of basti, patient revealed significant improvement.